2012
DOI: 10.1182/blood.v120.21.88.88
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extracranial Internal Carotid Arteriopathy in Stroke-Free SCA-Children: A New Risk Factor for Silent Strokes

Abstract: 88 Background. Strokes are a well-known complication of sickle-cell anemia (SCA), and are largely due to intracranial arteriopathy, detected by routine transcranial Doppler (TCD). Adams et al. showed in the STOP I trial (N Engl J Med, 1998) the efficiency of transfusion programs for primary stroke prevention in patients identified by TCD as being at risk of stroke. We recently reported in the CHIC newborn cohort (Bernaudin et al., Blood, 2011) that early TCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The cumulative incidence of silent infarcts was 37% by age 14 years in a newborn cohort that had early assessment by TCD and transfusion in case of abnormal TCD, suggesting that TCD screening does not detect all SCA‐patients at risk for silent cerebral infarcts and highlighting the need for identification of additional risk factors. Recent publications reported the implication of extracranial internal carotid arteriopathy on the risk for overt stroke in SCA‐patients (Calviere et al , ; Gorman et al , ; Deane et al , ) and it was shown that intracranial and extracranial stenoses were independently and significantly associated with the risk for silent infarcts (Verlhac et al , ) and that extracranial stenoses were significantly associated with severe anaemia and tortuosities, (more frequent in males). These findings confirm previous reports (Bernaudin et al , ,b) showing that intracranial stenoses, severe anaemia and male gender were independent and significant risk factors for silent infarcts.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cumulative incidence of silent infarcts was 37% by age 14 years in a newborn cohort that had early assessment by TCD and transfusion in case of abnormal TCD, suggesting that TCD screening does not detect all SCA‐patients at risk for silent cerebral infarcts and highlighting the need for identification of additional risk factors. Recent publications reported the implication of extracranial internal carotid arteriopathy on the risk for overt stroke in SCA‐patients (Calviere et al , ; Gorman et al , ; Deane et al , ) and it was shown that intracranial and extracranial stenoses were independently and significantly associated with the risk for silent infarcts (Verlhac et al , ) and that extracranial stenoses were significantly associated with severe anaemia and tortuosities, (more frequent in males). These findings confirm previous reports (Bernaudin et al , ,b) showing that intracranial stenoses, severe anaemia and male gender were independent and significant risk factors for silent infarcts.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…It can be hypothesized (Fig ) that absence of α‐thalassaemia, G6PD deficiency, severe anaemia and haemolysis are risk factors for abnormal TCD, which is a risk factor for intracranial stenosis, itself a risk factor for silent infarct. Moreover, extracranial internal carotid tortuosities, which are more frequent in boys are risk factors for extracranial stenoses, themselves associated with the presence of silent infarcts (Verlhac et al , ). Clinical factors, such as ACS, have been shown to be significantly associated with stroke (Ohene‐Frempong et al , ) and elevated systolic blood pressure with stroke (Ohene‐Frempong et al , ) and silent cerebral infarcts (DeBaun et al , ) whereas acute anaemia episodes were significantly associated with acute silent cerebral infarcts (Quinn & Dowling, ).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation